Luminescence OLED Technology and Applications - Pyshkin, Sergei (IntechOpen, 2020)
Luminescence - OLED Technology and Applications is a collection of reviewed and relevant research chapters offering a comprehensive overview of recent developments in the field of organic light-emitting diode (OLED) materials and devices. The book comprises chapters authored by various researchers and is edited by an expert in the field. It provides a thorough overview of the latest technologies and applications in this field and opens new possible research paths for further novel developments.